The Global Maritime Fulcrum as A Strategic Narrative: A Critical Examination of Its Emergence, Conveyance, and Decline in Indonesian Strategic Discourse - Agastia, I Gusti Bagus Dharma (Muslim Politics Review, 2023)
In 2014, President Joko ‘Jokowi’ Widodo declared he would lead Indonesia, the most populous Muslim nation on earth, to become a ‘global maritime fulcrum’ (GMF). His announcement was taken as a sign of Indonesia’s commitment to be a more active participant in regional maritime security. This nascent maritime vision, however, suffers from endogenous flaws, ranging from personal leadership to widespread bureaucratic deficiencies, culminating in its recession from Indonesian political discourse. This paper seeks to understand how and why the GMF receded from political discourse through the lens of strategic narrative. It finds that technocratic appeal serves as a stronger legitimating method of the GMF compared to other forms, which is due to agential preferences aligning with domestic structural conditions, resulting in development narratives being favoured over maritime-related narratives. The relationship results in government priorities being skewed towards the infrastructure aspect of the GMF at the cost of the other aspects. To demonstrate this argument, this paper analyses an original dataset of 267 speeches and statements, both in English and Indonesian, delivered by key government officials related to formulating and implementing the GMF concept from 2014 to 2021, in addition to relevant policy documents.